Pertimbangan Hakim terhadap Khulu' karena Suami Melanggar Taklik Talak Perspektif Mazhab Syafi'i: Analisis Putusan No.219/Pdt.G/2024/PA.Ska - Anisah Nadila; Bagus Ramadi (CV Global Research Publication, 2026)
This study aims to analyze the judges' legal reasoning in determining such a violation as the basis for granting a khulu' divorce in Decision Number 219/Pdt.G/2024/PA.Ska, and assess the conformity of the judicial reasoning with the principles of the Shafi'i school. This research employs a normative legal research method using statutory, case, and conceptual approaches. The data were collected through library research and document analysis of court decisions, statutory regulations, classical Shafi'i jurisprudential texts, and relevant scholarly literature. The data were then analyzed qualitatively using a deductive method. The findings reveal that, according to the Shafi'i school, the violation of the Sighat taklik talak constitutes a form of ṭalāq mu'allaq (conditional divorce), whereby the divorce automatically takes effect once the stipulated condition is fulfilled, resulting in a revocable divorce (ṭalāq raj‘ī). Meanwhile, the panel of judges in Decision Number 219/Pdt.G/2024/PA.Ska recognized the violation of the conditional divorce pledge as valid grounds for granting a khulu' divorce with ‘iwaḍ based on the provisions of the Indonesian Compilation of Islamic Law and the facts established during the trial. This study concludes that while the judges' reasoning is consistent with Indonesian positive law, it does not fully correspond to the doctrinal framework of the Shafi'i school, reflecting an adaptation of classical Islamic jurisprudence within the practice of Indonesia's Religious Courts. These findings indicate the need to harmonize the Compilation of Islamic Law (KHI) and Shafi'i jurisprudence in judicial practice.